A tribute to Stephen King: Hispanic gothic and cultural globalization. Issue 2 (1st October 2019) - Ordiz, Inés
King: Homenaje al rey del terror (King: Homage to the King of Terror) (Cáceres, 2018) is an anthology of short stories written by Latin American and Spanish young authors in tribute to Stephen King and compiled by Ecuadorian writer Jorge Luis Cáceres. The anthology has been published in Ecuador, Mexico, Peru, Chile, Argentina and Spain, and some of the texts in the collection have been translated into English by the online webzine Palabras Errantes. The stories illustrate some of the new directions that contemporary Latin American and Spanish cultural production are taking, such as the exploration of non-mimetic forms of fiction (other than magical realism), the embracing of international influences and the understanding of the local in relation to the global. As a tribute to 'the king of terror', the short narratives collected in the anthology use resources of the Gothic, horror, the fantastic and science fiction; I concentrate my analysis on the first two. My reading of the Gothic and horror devices in the stories is informed by recent criticism on the gothic mode, as well as contemporary theories of cultural globalization and glocalization. The aim is to recognize and analyse the processes of translation, circulation, deterritorialization and multiterritorialization exemplified in the narratives, and the different ways in which these processes define contemporary Hispanic Gothic.